BUILDING A VIRTUAL HAND FOR SIMULATION - Hidayat, Muhammad Agung (International Humanities and Applied Science Journal, 2018)
In this paper, one of the advanced technology in the field of human-computer interaction is known as the virtual hand. At the first, we have to know the grasping behavior.Â  The virtual hand simulation can give experience grasping behavior and natural interaction. Many of HCI researcher said that one day the interaction between human and computer will be more natural, easy to use and less error. We only focus on 3D hand gesture. We use the engaging virtual application that supports 3D hand gesture in order to test whether the combination of grasping will provide the desired effect or not. We present the result from usability evaluation experiments. And finally, we want to shows that theÂ  3D hand gesture can be grasping naturally look like the human hand.